Evidence of intraplate magmatism and subduction magmatism during the formation of Nagaland–Manipur Ophiolites, Indo–Myanmar Orogenic Belt, north‐east India. Issue 2 (3rd January 2022) - Imtisunep, Sashimeren; Singh, Athokpam Krishnakanta; Bikramaditya, Rajkumar; Khogenkumar, Shoraisam; Chaubey, Monika; Kumar, Naveen
Abstract : Mafic extrusive rocks (basalts) and intrusive rocks (gabbros) from the Nagaland–Manipur Ophiolite (NMO) of the Indo–Myanmar Orogenic Belt (IMOB), north‐east India, are investigated to understand their magmatic evolution in diverse tectonic environments. Basalts are distinguished into two types: basalt‐I and basalt‐II. Basalt‐I type shows the sub‐alkaline character with Nb/Y < 0.50, low Nb/Th (2.36–7.94), and low to moderate La/Sm (1.00–4.12) indicating derivation from a slightly enriched mantle source and also supported by their enriched LREE pattern with flat HREE. They are depleted in HFSEs (Nb and Ti) but enriched in U and Pb, which is indicative of a typical subduction origin derived from an MORB‐type mantle source. Investigated samples of basalt‐II and gabbros have an equal composition with alkaline characteristics. They have Nb/Y > 0.50, high Nb/Th (8.38–13.37), and highly enriched LREE (La/Sm = 4.41–6.35) pattern. They show typical Ocean Island Basalt (OIB) characters of a plume source. The two sets of basalts and gabbros found in this study have no sign of genetic relationship, and therefore, it strongly suggests that they were derived from two different mantle sources of a plume and a subduction zone mantle wedge. Our study supports the theory that the NMO has records of different magmatic episodes produced ranging from plume‐related magmatism, to divergent and convergent plate magmatism that were generated at diverse tectonic settings. Abstract : This article presents comprehensive geochemical data of two diverse mafic rocks (basalts and gabbros) from the Nagaland–Manipur Ophiolites of north‐east India and discusses their magmatic evolution. Basalts are distinguished as basalt type‐I that shows the sub‐alkaline character with Nb/Y < 0.50, low Nb/Th (2.36–7.94), and low to moderate La/Sm (1.00–4.12) indicating derivation from a slightly enriched mantle source, whereas basalt type II and gabbros have Nb/Y > 0.50, high Nb/Th (8.38–13.37), and highly enriched LREE (La/Sm = 4.41–6.35) pattern and exhibit typical Ocean Island Basalt (OIB) characters of a plume source. The two sets of basalts found in this study have no sign of genetic relationship, and therefore, it strongly suggests that they were derived from two different mantle sources of a plume and a subduction zone mantle wedge.